In vitro evaluation of the neuroprotective potential of Olea dioica against Aβ peptide-induced toxicity in human neuroblastoma SH-SY5Y cells - Kenchappa, Pratap G.; Karthik, Yalpi; Vijendra, Poornima D.; Hallur, Raghavendra L. S.; Khandagale, Ajay S.; Pandurangan, Ashok K.; Jayanna, Sathisha G.; Alshehri, Mohammed Ali; Alasmari, Abdulrahman; Sayed, Samy; Shantaram, Manjula; Mushtaq, Muntazir (Frontiers in Pharmacology, 2023)
Alzheimer’s disease (AD) is a type of neurodegenerative disease, associated with the hastening of ROS, acetylcholinesterase (AChE) activity, and amyloid β peptides plaques in the brain. The limitations and side effects of existing synthetic drugs incline toward natural sources. In the present communication active principles of methanolic extract of Olea dioica Roxb, leaves are explored as an antioxidant, AChE inhibitor, and anti-amyloidogenic. Furthermore, neuroprotection against the amyloid beta-peptide has been studied. The bioactive principles were identified by GC-MS and LC-MS and further subjected to antioxidant (DPPH and FRAP) and neuroprotection (AChE inhibition, ThT binding, and MTT assay, DCFH-DA and lipid peroxidation (LPO) assay using neuroblastoma (SHSY-5Y) cell lines) assays. Methanolic extract of O. dioica Roxb. leaves was found to contain polyphenols and flavonoids. In vitro assays exhibited potential antioxidant and anti-AChE activities. ThT binding assay indicated protection against amyloid-beta aggregation. MTT assay, Aβ1-40 (60 µg/mL) with extract showed significant cytotoxicity to SHSY-5Y cells. ROS level significantly decreased in the Aβ1-40 (40µg/mL) + extract (15 and 20µg/mL) and LPO assay suggesting prevention of cell damage. Results advocate that O. dioica leaves are a good source of antioxidants, anti-AChE, and anti-amyloidogenic compounds which may be further evaluated as a natural medicine for the treatment of AD.